Pendampingan UMKM dalam Membangun Citra dan Strategi Promosi Efektif pada Gerakan Pemuda Ansor Pagedangan Tangerang - Asep Sulaeman; Reza Khairul Hadi; Komarudin Komarudin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting local economic development; however, many MSME actors still face challenges in building a strong business image and implementing effective promotional strategies. This community service activity was conducted to assist MSME actors of Gerakan Pemuda Ansor in Pagedangan, Tangerang, in strengthening business identity, improving promotional capabilities, and expanding their understanding of effective marketing strategies. The activity was conducted in Pagedangan Village, Tangerang, on April 19, 2026. The community service team consisted of three lecturers from Universitas Pamulang, with 17 MSME participants from Gerakan Pemuda Ansor. The implementation method consisted of three main stages: preparation, implementation, and reporting. The implementation stage used several approaches, including material presentation, practical activities, discussions, and question-and-answer sessions. The materials focused on building a positive business image, developing attractive promotional content, and selecting appropriate promotional strategies according to the characteristics of the target market. The results showed that participants gained improved understanding of the importance of business image and promotional strategies in increasing product attractiveness and competitiveness. Participants were also able to identify opportunities to improve their business branding and promotional practices. The activity was therefore considered useful in increasing MSME participants' knowledge and practical skills in developing sustainable promotional strategies.